Risk of Coronavirus Disease 2019 (COVID-19) in Special Military Operations in Southern Thailand, 2021 - Thongsawang, Tawan; Sawangsrisutikul, Kanokkarn; Hongchan, Phatcharida; Plernprom, Patchanee; Thongsom, Pattheenunt; Pingkan, Paratthakorn; Waeche, Sareena; Waeduera-oh, Zainab; Mokmula, Mahamad; Nittayasoot, Natthaprang; Suphanchaimat, Rapeepong (OSIR Journal, 2023)
On 12 Oct 2021, the Department of Disease Control received a notification of a coronavirus disease 2019 (COVID-19) cluster in a military camp in Southern Thailand. In collaboration with local health authorities, we investigated the outbreak to describe case characteristics, identify risk factors, and provide control measures. We conducted a descriptive study by reviewing laboratory results and medical records and interviewing the cases and military staff. A retrospective cohort study was undertaken to determine the potential risk of COVID-19 by Poisson regression with robust standard errors. Of 188 military personnel, 37 were confirmed cases (attack rate 19.7%). The attack rates among males and females were 28.97% and 10.71%, respectively. Most cases (97.3%; 36/37) had mild symptoms and one was asymptomatic. Attending a special operation in communities or forest (adjusted risk ratio (RR) 2.75 [95% CI 1.60–4.75]) and engaging in high-risk behaviors (adjusted RR 3.41 [95% CI 1.64–7.06]) were risk factors, while completing 2-dose vaccination schedule had a tendency to prevent COVID-19 infection. We recommend the implementation of strict symptom monitoring measures among special operation forces, efforts to promote personal hygiene, and we encourage all military staff to undergo full vaccination. Keywords:  COVID-19, military camp, vaccine, Thailand